2020
DOI: 10.1186/s12915-020-00903-3
|View full text |Cite
|
Sign up to set email alerts
|

Colored visual stimuli evoke spectrally tuned neuronal responses across the central nervous system of zebrafish larvae

Abstract: Background Visually guided behaviors such as optomotor and optokinetic responses, phototaxis, and prey capture are crucial for survival in zebrafish and become apparent after just a few days of development. Color vision, which in zebrafish is based on a spatially anisotropic tetrachromatic retina, provides an additional important component of world representation driving fundamental larval behaviors. However, little is known about the central nervous system (CNS) circuitry underlying color visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Most notably, the retina's acute zone ( 25) is dominated by UV-sensitive circuits (13). Here, most bipolar cell terminals respond primarily to UV-stimulation, and only some in addition respond to other wavelengths ( 13)a general pattern that is recapitulated also at the level of the retinal ganglion cells (24) to drive a strong UV-response in the brain (47,55,56) which filters all the way to spinal circuits (56,57). Nevertheless, despite this profound functional dominance, no anatomical study has reported the presence of UV-cone-dedicated bipolar cells, as for example in the case of greencones (49) (see above).…”
Section: A Private Channel For Detecting Uv-signals?mentioning
confidence: 99%
“…Most notably, the retina's acute zone ( 25) is dominated by UV-sensitive circuits (13). Here, most bipolar cell terminals respond primarily to UV-stimulation, and only some in addition respond to other wavelengths ( 13)a general pattern that is recapitulated also at the level of the retinal ganglion cells (24) to drive a strong UV-response in the brain (47,55,56) which filters all the way to spinal circuits (56,57). Nevertheless, despite this profound functional dominance, no anatomical study has reported the presence of UV-cone-dedicated bipolar cells, as for example in the case of greencones (49) (see above).…”
Section: A Private Channel For Detecting Uv-signals?mentioning
confidence: 99%
“…Until very recently, spectral processing in the larval zebrafish brain had received little attention -that is, until 2020, which saw three independent imaging studies appear quasi-simultaneously 32,88,92 , all asking the same key question: how do neurons in the tectum, and the rest of the brain, respond to spectrally distinct stimuli? The results from these studies, which are largely in agreement with each other, confirmed and extended our previous understanding from diverse species of adult cyprinids: Sensitivity is far from uniform over the fish-visible spectrum, instead showing a clear dominance of UV-and long-wavelength responses over mid-wavelengths (Figure 5E,F).…”
Section: Retinal Ganglion Cellsmentioning
confidence: 99%
“…This link was already suggested based on the dominant presence of UV-On circuits in the retina's acute zone 33,35 and the demonstration that the corresponding upper-frontal part of visual space is critical for behavioural performance [104][105][106] . In fact, this acute-zone UV-dominance begins as early as the development of cones and is one of the most pervasive features of zebrafish spectral processing throughout the entire visual system 32,33,35,40,43,88,92 including the spinal cord 92,107 .…”
Section: From Cones To Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Recordings revealed that, despite some expected variation 2 , 3 , 4 (for example, Figure S1 B), neural responses in all major visual centres of the brain had a common, overarching spectral sensitivity profile: UV-On, Blue/Green Off, Red On-Off ( Figure 1 B). This organisation into three spectral processing zones (UV, Blue/Green, Red) can be linked to visual ecology.…”
Section: Main Textmentioning
confidence: 99%